Fostering Creative Thinking Skills through Project-Based Learning Learning Models in Nutritional Balance Practices of High School Students - Ismi Senjayani (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2021)
This study aims to identify the improvement of students' creative thinking skills through the Project Based Learning model. The method used was a quasi-experimental pretest-posttest one group design. In this case the test before treatment and after treatment was used and did not use the comparison class. The research subjects were 36 students of class XI IPS 2 in the 2019/2020 academic year, with research material on balanced nutrition practices. The research data obtained came from the analysis of the observation sheet during the learning process and the description questions in the pretest-posttest. The data collected were analyzed using the percentage technique and processed descriptively. From the analysis process, it was shown that there were differences in students' creative thinking skills before and after being treated with PjBL. There is an increase in the percentage of all indicators of creative thinking skills consisting of flexibility, fluency, originality and elaboration. Based on the research results, it can be concluded that the Poject Based Learning learning model can improve students' creative thinking skills in balanced nutrition practice activities.